SAYURI’S DEFENSE MECHANISM IN ARTHUR GOLDEN’S MEMOIRS OF GEISHA - ERA KARTIKA SARI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2013)
Abstrak Penelitian ini berfokus pada novel Athur Golden yang berjudul Memoirs of Geisha untuk menjawab : mekanisme pertahanan diri apa saja yang digunakan oleh tokoh utama? Mengapa tokoh utama menggunakan mekanisme pertahanan diri? Dengan konsep mekanisme pertahanan diri masalah akan dianalisis. Penelitian ini menggunakan mekanisme pertahanan diri untuk menghadapi kenyataan dan kecemasan tokoh utama. Kecemasan Sayuri berawal dari latar belakang keluarga dan lingkungan Sayuri. Keluarga tidak memenuhi hasratnya dan menyebabkan kekecewaann. Hasrat Sayuri untuk mendapatkan kasih sayang, rasa aman, dan kebebasan. Data ini menyajikan mekanisme pertahanan diri Sayuri untuk menghadapi kecemasannya dan dapat hidup dengan bahagia. Sayuri juga menggunakan mekanisme pertahanan diri untuk memecahkan masalahnya. Dengan mekanisme pertahanan diri Sayuri dapat beradaptasi dengan lingkungan yang baru serta menjadi seorang geisha yang terkenal. Kata kunci : Mekanisme pertahanan diri, represi, supresi, rasionalisasi, bertindak Abstract This research was conducted to explore Arthur Golden’s Memoirs of Geisha in order to answer the following research questions: what kind of defense mechanisms used by main characters? Why does Sayuri use defense mechanisms? The concept of defense mechanisms was employed as a framework for analysis. The study disclosed that Golden used repression, suppression, rationalization, and acting out because she had realistic and moral anxiety. Her anxiety was from family background and society. Her families did not fulfill her desires which brought her to have anxiety. Sayuri desired for parental love, safety and freedom. In addition, the society wanted her to follow social life which was against her desires. The society wanted Sayuri to be civilized while Sayuri herself wanted to be independent and freedom. Therefore, she repressed her anxiety in order to live peacefully. Furthermore, Sayuri used suppression because she faced unavoidably threatening situations. Sayuri had to live in the house of Okiya where she was forced to comply with social norm which was against her natural behaviors. Sayuri had conflict when she allowed the conmen to be a geisha during the journey although she did not want to. Sayuri suppressed her anxiety in order to overcome these situations. Besides, her defense mechanism also emerges as a result of her failure of her childhood when she lost her family. Importantly, defense mechanisms led the characters to experience new things and new people and helped Sayuri to reach their maturity. Keywords : Defense mechanism, repression, suppression, rationalization, and acting out INTRODUCTION Literature is one of the most creative and universal means to communicate the emotion, spiritual and intellectual concern of mankind. Sometimes most of the students feel that literature is a terrible subject and makes them nervous to study it. However, literature will be an interesting thing or not depends on their feeling of sensitivity and their imagination to enjoy the beauty of literature. In addition, literature is one way to express the creativity that reveals the interest and values of the society and frequently gives intimate and unique glimpses of how people live. (1) Statement of the problem What kind of defense mechanism is used by the main character in Arthur Golden’s Memoirs of Geisha? Why does Sayuri use defense mechanism in Arthur Golden’s Memoirs of Geisha? (2) Solving problem plan In writing the thesis, the thesis collects two types of data. They are main data and supporting data. The main data are taken from novel Memoirs of Geisha written by Arthur Golden that was published in 1999. The supporting data are taken from comments and critics about that novel which the thesis gets from internet. The thesis also taken from a lot of books as references. They are: Approach to Literature by Graham Little, Literature: Introduction to Reading and Writing by Edgar V. Robert and Henry Jacobs; A Handbook to Literature by C. Holman and William Harmon; Literature Structure, Sound, and Sense by Perrine, Peck and Cayle; An Introduction of Literature Approach by James H. Pickering, and also the psychological books that have correlation with the topic. (3) Purpose of the research To depict Sayuri’s defense mechanism in Arthur Golden’s Memoirs of Geisha, To reveal the reason why Sayuri use defense mechanism in Arthur Golden’s Memoirs of Geisha. (4) Summary about the theories This study focused on analyzing protagonists’defense mechanisms in Arthur Golden’s Memoirs of Geisha. Moreover, the results defense mechanisms the main character was included. Therefore, the theoretical framework of this study was drawn. This part consist comprises the concept of anxiety and theory of defense mechanisms. Normally when a person has some problems, she will automatically find a proper way to deal with them. However, some problems are more troublesome for some people than for other people. Those troubles lead to the anxiety state. According to James R. Gallagher and Herbert I. Harris, anxiety can occur at a deep, unconscious level and be noticed with some symptoms of physical illness. It can also happen very close to conscious level. It can be observed through body responses. For example, when an individual faces anxiety, she may have a dry mouth, rapid breathing, fast heart rate, dilate pupils or even taut muscle. This idea is similar to that of Max L. Hutt and Robert Gwyn Gibby. They state that anxiety tends to be transformed in many forms of symptomatic disturbance. It may not be able to be recognized. According to Sigmund Freud, defense mechanisms are the devices that ego defends itself against conflicts and anxieties by forcing unpleasant thoughts and impulses to the unconscious level. According to the definitions, it is obvious that defense mechanisms are psychological devices adopted by an individual to cope with frustrations, anxieties, stresses and conflicts. They can happen at the level of unconsciousness. They serve to protect the individual’s self-esteem and help extend time for direct problem solving. Appropriate use of defense mechanisms can make the individual live happily in the society. Defense mechanisms are necessary for people living in any society. They are important for personality development. To know their characteristics and functions will enable us to have a better understanding of defense mechanisms. Krench suggests the characteristics of defense mechanisms as follows. They are devices adopted to protect individual’s self-esteem and to defend against anxiety when the individual encounters continuing frustrations. They have both negative and positive aspects. For the negative aspect, they are the ways to avoid or protect the individual from anxiety. For the positive aspect, they help compensate mind and maintain self-esteem. Each device carries the same common quality which is self-deception. Then the mechanisms reveal in the form of denial of needs, feelings and situations that can cause anxiety or losing face. They can also reveal in the form of disguise of needs and motivations to substitution or reaction formation in order to be socially accepted. Normal people use defense mechanisms in some ways. An appropriate use is satisfied but an overuse is dangerous because they can cause neurotic phenomena. Each device of defense mechanism is co-related. This means the functions of each mechanism are overlapped. It is difficult to completely specify one from the others. To make it understandable, psychologists put them in categories. However, in order to cope with unpleasant feelings, the individual may have to use more than one mechanism. Naming is just to make it easy to describe. To better understand the employment of defense mechanisms, the needs of individual must be symmetrically analyzed. Defense mechanisms are not solutions for problem solving. Their function is to protect the individual from anxiety which comes from conflicts, frustrations and threatening. Apparently, it can be concluded that defense mechanisms are employed by normal people in their everyday lives. They help maintain self-esteem and protect the individual from unpleasant or undesirable feelings. They are not the solutions for a direct problem solving. The moderate use is satisfaction, but if the individual uses particular mechanism more often, it can cause mental disorder. Defense mechanisms are important for everyday life, so they have been applied to study human behaviors in research. Although many psychologists study on defense mechanisms, they give similar concepts of defense mechanisms. METHOD The thesis applies qualitative research in which the research is nor based on the statistics and mathematics, in this research, the research is focused on the depth or the quality of interaction between the concepts that is used in analyzing the topic. Since the research deals with literary work, in analyzing the topic, the thesis would like to use instric approach and extrinsic approach. According the Rene Wellek and Austen Warren in their book Theory of Literature (1756:73), intrinsic approach is an approach that emphasizes elements of literature itself. It covers plot, character, conflict, and so on. It can be concluded that instrinsic approach is the approach which is focused on the elements of the novel itself, such as plot, character, conflict. Rene Wellek and Austen Warren in their book Theory of Literature (1756:73), extrinsic approach is the approach that concerns other fields of study. It means that extrinsic approach is used to analyze the literary work by connecting the work with other fields of study, such as sociology, anthropology, psychology, religion, or other sciences. In analyzing this topic, the thesis apllies psychological approach, because in answering the statement of the problem, the thesis needs psychological knowledge since the problem concerns with human psychology. In writing the thesis, the thesis collects two types of data. They are main data and supporting data. The main data are taken from novel Memoirs of Geisha written by Arthur Golden that was published in 1999. The supporting data are taken from comments and critics about that novel which the thesis gets from internet. The thesis also taken from a lot of books as references. They are: Approach to Literature by Graham Little, Literature: Introduction to Reading and Writing by Edgar V. Robert and Henry Jacobs; A Handbook to Literature by C. Holman and William Harmon; Literature Structure, Sound, and Sense by Perrine, Peck and Cayle; An Introduction of Literature Approach by James H. Pickering, and also the psychological books that have correlation with the topic. In collecting data, the thesis condacts library research that is the research that is done in library and in the room. In this research all the main data and the supporting data are taken by close reading. When reading the books, This study make quotations and notes from the books. After the data have been collected,the study are select and classfies the data related to the topic. The data that have been selected and classified are anlyzed by interpreting them. All the data are explained and described clearly. The thesis applies the deductive and inductive method of writing. According to Graham Little (1966:201) in Approach to Literature state: “ Deducative is the process is reasoning from the general principles to particular conclussion. Inductive is the opposite process one in which many examples are considered, leading to the formation of a general principles in summary of all the evidence.” The quatation means that deductive method is done by presenting general idea which is proved by the quotations. While, inductive method is written by presenting, the quotation which is explained by statements. ANALYSIS AND RESULT Sayuri’s Defense Mechanism in Arthur Golden’s Memoirs of Geisha Psychologically, the characters in novel Memoirs of Geisha always haunted by anxiety, psychological conflict, powerless to face reality in external of her self (environment). Moreover, in data analysis, the writer focuses on certain characters who are dominating the plot of the story on novel Memoirs of Geisha. Besides that, she fulfill rules and regulations to be analyzed from Freudian psychoanalytic theory because having tragic and dramatic psychological process. In this analysis, this research is about the defense mechanism to cover someone’s feeling from tension. It is used by Sayuri who is the main character of this novel. Defense mechanism appears because of some reasons that make people feel in danger. It is a way to protect people from unpleasant emotions and keep unwanted thoughts from the unconscious mind. In this novel, the main character Sayuri uses some defense mechanisms to protect her from any kind of conflicts that occur in her life. Here, Sayuri has identified four types of defense mechanisms in this study. Sayuri’s Id In tracing Sayuri’s life, it found that she has both realistic and moral anxiety. Sayuri’s realistic anxiety comes from her family and society while her moral anxiety is from her moral awareness. In the beginning of the story, Golden describes Sayuri as a child who was sold by Mr.Tanaka. In addition, the human instinct of Sayuri comes up in the form of looking for herself, asking herself and seeking for answer how I was sold and why? "I couldn't stop thinking about Mr. Tanaka. He had taken me from my mother and father, sold me into slavery, sold my sister into something even worse. I had taken him for a kind man. I had thought he was so refined, so worldly. What a stupid child I had been! I would never go back, it would only be to tell Mr. Tanaka how much I hated him." (Arthur Golden, 1997:94) From the narration above, Sayuri has a beloved sister in childhood whom she loves her so much. Unfortunately, she sold because their family poor. Sayuri cannot accept and makes her can not forget about it. She was frustrated and sad because she always thought of her. This study describes above how the strongest unconscious drive (the id) of Sayuri appears by looking for answer about her own self. Actually, it usually happens to everyone in the world. In this case, Sayuri just keeps asking to herself every time. This condition appears more complex when she has known that she was born for specific purpose, to pay her family debts. The inner conflict of Id and ego, here, arise rapidly in the form of human’s right that should be felt by Sayuri as a human kind. In this case, Sayuri was confused because she felt the anxiety after sold by House of Okiya. She could not fulfill her desire to her beloved family anymore. So, she tried to look for away to reduce her painful memory. "When you begin working as a geisha, you'll pay the Okiya back for it, along with everything else you'll owe. Your meals and lessons; if you get sick, your doctor's fees you pay all of that yourself. Why do you thing mother spend all her time in her room, writing numbers in those little books. You owe the Okiya even for the money it cost to acquire you." (Arthur Golden, 1997:88) The data above describe that illustration that the combination of precious genetic material explains that Sayuri never has her life utterly, she must be ready when become a geisha. On the other hand, Sayuri is a human kind that has a right of life; it is the real and whatever the reasons she has right to posses herself utterly. This consciousness came up from the unconscious world of human kind. Sayuri’s Ego In the case of human’s ego, the tools we use to deny and distort reality and to defend our ego against anxiety that are called by “Ego Defense Mechanism” protect us from excessive neurotic anxiety and insure the health, safety and "sanity" of the personality. The conflict of Sayuri’s ego begins when she has known about her existent in this world that being a geisha. She was so confused about herself; she wants to be free from the habitual action to go to the house of Okiya. In addition, her ego pushes herself to take an action for herself. Sayuri’s ego supresses on to make decision what will act to save her and make everything comfortable. Her decision is clearly comes from the impulse of her ego. “decision about me is being made, and no one's bothered to ask the one person who most deserves it to speak her opinion. There's way too much to explain, and so I do the best I can. "It's not God. Just me," I say. "I want to sue them for the rights to my own body" (Arthur Golden, 1997:21). The quotation above shows people how the ego of Sayuri supresses her on having herself utterly. The illustration above indicates, although she is not sure anymore caused any consideration, Sayuri is still in her decision and she does not change her mindt. This inner conflict arise more complex, Sayuri think s that she was mature enough to make decision based on her. Sayuri’s Superego Establishment of the superego persisted in the internalization process of the moral where guides exist in the external self the individual to the moral where guides exist in the internal self of individual. Then it is described that this internalization process besides persisted by the way of individual identification. But by using other way too, that is by rationalization, acting out, and defense mechanism of the ego. These ways are done by individual in effort to compromise about impulses from the id with demand of the superego. By playing the role of the ego as executive of personality, the individual creates the balance in personality; so that it enables to deal with external world well and effective. Rationalization is another device of defense mechanism used by Sayuri. Sayuri rationalizes because she encounters conflicts, especially when she decides to be a geisha. Rationalization belongs to the mechanism of deception. It is the way that an individual gives reasons for doing something in order to be socially accepted or to avoid punishment, such as when making certain decisions. Rationalization is then built into an individual’s behavior as a protective mechanism. When doing something, a person will come up with plausible reasons believing that she is not be blamed from such behavior. The user may not realize that she is twisting the facts to protect the self-esteem by the way of rationalization since it is quite unconscious. However, the overuse of rationalization may take a person away from the real problems that she may end up with crisis which cannot be solved. Sayuri makes use of rationalization several times during her journey when she wants to be a geisha. Actually, Sayuri decided to be a geisha for some reasons. CONCLUSION Based on the whole analysis of this study in chapter3, there are several conclusions in line with the statement of the problems. Base on type of defense mechanism by Sigmund Freud, there are four types depicted on the main character Sayuri .The dominant are repression, suppression, rationalization, and acting out. Sayuri’s repression reflects maincharacter’s effort to look for the substitute object as the replacement. Sayuri needs substitute object to get satisfaction of her desire. It aims to reduce the impulse of her past experiences with her beloved sister Satsu. It occurs when she losses her beloved sister in childhood, Sayuri represses that she dislikes her family because she has family problems. She is sold by Mr. Tanaka to pay her father’s debts. From the previous chapter, Sayuri’s family does not fulfill her desires. Sayuri quests for parental love while her father wants to control her as a property. Generally, the family is considered a place for safety and understanding; however, for Sayuri, it is the place that she gains painful feelings, especially from her brutal father. Sayuri has to repress her anxiety because she is forced to live with Nitta Sayuri (mother of Okiya). The repressed impulse forces Sayuri to escape. The fact that she faces difficulties when she works at Okiya. She must endure physical burden and physiological burden. Her physical burden, she endures concern with the heavy task she has to do in her daily activities, while the psychological burden, she endures is faced when she get the supression from Hatsumomo. In the facing those burdens, she never stops but she keeps struggling to get the better life, that Sayuri has done can be related with defense to dream to get the better life, and to reach this aim she should struggle hard. In other way, she also uses rationalization to reduce her anxiety by joining the group to learn a positive activity. It can help her to learn her situation emotionally so she can decrease the emotion and the impulse that make her frustrated. Besides, she uses rationalization to cover herself from people arround her who ask about psychological issue. It aims to help her condition and cover up the truth. She does not want people to know the truth because people will understand the reality that is happened by Sayuri. This type of defense mechanism is usually used to protect people from the real situation that is able to make them safe. In this way, people who use defense mechanism need the reasons make sense or the rational statement. Rationalization is commonly use when people get a problem emergently so they need rational thought to answer or avoid the case. The last ego defense mechanism that is used by Sayuri is acting out. Sayuri uses this defense mechanism in the last of the story. She is really confused and frustrated when Satsu loss. She keeps the anger and after knows the cause of Satsu lost. Sayuri’s defense to be a geisha is proved by the events faced by Sayuri in dealing with the hard reality of her new life. Sayuri must receives the reality that she does not live with her parents anymore. Sayuri tries to get the better life by learning the stages of geisha including to learn instrument music, dance, tea ceremony and etc. Sayuri is not only brings the happiness but also the sadness on herself. Sayuri becomes more mature in life. The happy effect that Sayuri gets are she becomes a successful geisha with the highest price and she is able to repay all of her debts in Okiya and Sayuri’s dream come true with the Chairman. The sad effect happens on Sayuri is Sayuri must be willingly to let her mizuage go to be taken by another man. Sayuri causes of using defense mechanism is the second statement of problem which has been identified. There two causes has been identified, they are trauma, stress and anxiety. Those factors that make Sayuri used defense mechanism. Based on the first statement of the problem it can be concluded that Sayuri uses defense mechanisms to reduce or cover the painful mind from tension to remind her miserable memory. In this way, it helps the main character from the uncomfortable situation. Traum acan be the reason of using defense mechanism because Sayuri lost her beloved sister and her parents in childhood, but she cannot accept it. She thinks that she can not live without them. Her trauma makes her feel anxious. The anxiety appears because Sayuri always reminds them and she cannot forget her memory with them. It makes her anxiety becomes bigger and it causes stress. Stress deals with anxiety. It is happened with Sayuri. She found the way to reduce her painful memories by using defense mechanism that has mentioned on the first analysis. Therefore, defense mechanism is the way how to protect herself from the miserable memory from her trauma, stress and anxiety.